2006
DOI: 10.1111/j.1365-2958.2006.05279.x
|View full text |Cite
|
Sign up to set email alerts
|

Pili with strong attachments: Gram‐positive bacteria do it differently

Abstract: SummaryBacteria attach to their appropriate environmental niche by using adhesins. To maximize their contact with the environment, adhesins are often present on the ends of long hairlike structures called pili. Recently, attention has focused on pili of Grampositive bacteria because they may be vaccine candidates in important human pathogens. These pili differ from the well-studied pili of Gram-negative bacteria because their subunits are covalently linked, they do not require specific chaperones for assembly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
148
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(152 citation statements)
references
References 31 publications
2
148
1
1
Order By: Relevance
“…Unlike the pilus-like appendages in Gram-negative bacteria, Gram-positive pili represent a polymerized assemblage of different protein subunits (called pilins), which are covalently linked by the transpeptidase action of sortase enzymes. There is only a limited understanding about the biological role of the Gram-positive pilus, although reports in pathogens are steadily increasing (28,32,35,37). Recently, we documented for the first time that surface piliation is associated with the probiotic L. rhamnosus GG (19,26).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the pilus-like appendages in Gram-negative bacteria, Gram-positive pili represent a polymerized assemblage of different protein subunits (called pilins), which are covalently linked by the transpeptidase action of sortase enzymes. There is only a limited understanding about the biological role of the Gram-positive pilus, although reports in pathogens are steadily increasing (28,32,35,37). Recently, we documented for the first time that surface piliation is associated with the probiotic L. rhamnosus GG (19,26).…”
Section: Discussionmentioning
confidence: 99%
“…MSHA is a member of the family of type IV pili, which had been suggested to be involved in attachment to the abiotic surface and is required for adhesion and biofilm formation in other bacteria (Watnich and Kolter, 1999;Hadi et al, 2012). Unlike other bacterial pili, which use as few as 2 proteins for assembly, type IV pilus biogenesis requires a dozen or more proteins (Scott and Zahner, 2006). Genetic and transcriptional analyses of the MSHA type IV pilus gene locus of the V. cholerae O1 EI Tor biotype revealed that 16 ORFs were required for MASH pilus biogenesis, these ORFs were designated mshA to mshQ (Marsh and Taylor, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Beneath their plain façade lies an exquisite helical architecture that provides for strength, flexibility and a multitude of functions, including twitching and gliding motility, adhesion, immune escape, DNA uptake, biofilm formation, microcolony formation, secretion, phage transduction and signal transduction. Unlike other bacterial pili, which use as few as two proteins for assembly [1,2], Type IV pilus biogenesis requires a dozen or more proteins, many of which share sequence conservation among divergent species. Pili are assembled, and in some cases disassembled, rapidly using powerful molecular motors that hydrolyze ATP.…”
Section: Introductionmentioning
confidence: 99%